Factors influencing the outcome of double valve replacement surgery - Gupta, Manju; Shoeb, Mohd; Mishra, Pankaj Kumar; Dhar, Sunil; Prasad, Jagdish (International Surgery Journal, 2017)
Background: Data on the influence of surgical variables in mortality and morbidity of patients undergoing double valve replacement (DVR) surgery are scarce. Objective of this study was to identify preoperative, intra operative and post operative factors associated with mortality and morbidity of patients undergoing DVR surgery. Methods: Between 2010 and 2016, patients who underwent double (Mitral and Aortic) valve replacement at our institution were analyzed. These patients were studied retrospectively for preoperative data and postoperative outcome including causes of deaths and the data was analyzed statistically. Results: There were 150 patients, 107 were male (71.3%) and 43 were female (28.6%) Present study revealed a high mortality rate among female patient undergoing DVR surgery than males, which is statically significant at p<0.05. Pre operatively 100 patients (66.6%) were class IV NYHA symptoms. This study finds a significant correlation between preoperative NYHA and hospital mortality with higher mortality rate in NYHA class IV patients with p-value <0.00001 which is significant at p<0.05. Long-term survival was also seen to be significantly dependent on the preoperative LVEF. Among intra operative parameter average total surgical time was 197.70 minutes (3.29 hours); average total cardio pulmonary bypass time was 82.67 minutes (1.37 hours) and average cross clamp time was 67.28 minutes (1.12 hours). Outcome groups (in-hospital death vs. hospital discharge) had a significant statistical difference in relation to variables, respectively: aortic cross clamp time (in minutes) of 77.66 and 67.40 (p=0.001); CPB 95.66 and 84.63 (p=0.006); and total surgical time 208.75 and 186.04 (p=0.002). Among the post operative complications, immediate complications occurring within 7 days of surgery were; low cardiac output syndrome in 9.3% (n=14), bleeding leading to exploration was 8% (n=12), refractory arrhythmias in 3% (n=5), sepsis in 4% (n=6) and acute renal failure in 2% (n=3). Inter mediate post-operative complications (7 to 30 days of surgery) were wound infection in 26 patients (17.3%). There was no incidence of stuck valve or pulmonary thrombo embolism Overall mortality was 8% (12 patients) all within 30 days of operation. There was no statistical difference between the outcome and the types of prostheses used, either biological or metallic (p=0.219). Conclusions: The study results have demonstrated a favourable survival outcome after DVR surgery. An advance age, female sex, a higher NYHA class, poor left ventricular function are associated with poor outcome. The operative mortality in patients undergoing DVR also depends on intra operative factors like total surgical time, CPB time and aortic cross clamped time and has improved remarkably over time, with the improvisation of extracorporeal circulation methods, myocardial protection techniques and postoperative management.